ASSESSMENT OF CEREBRAL BLOOD FLOW AND LEVEL OF CONSCIOUSNESS IN PATIENTS WITH THE SYNDROME OF ACUTE CEREBRAL FAILURE - Ніконов, В.В.; Білецький, О.В.; Курсов, С.В.; Феськов, О.Е.; Остапенко, В.М. (World of Medicine and Biology, 2019)
The article is devoted to the results of a reoencephalographic study on the compliance of the state of brain arterial blood flow with the level of consciousness in acute cerebral failure. The analysis and individual clinical observations of 116 patients with acute cerebral insufficiency syndrome are demonstrated. The examination was performed in patients with cerebral stroke, severe traumatic brain injury, discirculatory encephalopathy and postresuscitation disease. In most cases there is a very strong correlation between the intensity of the cerebral blood flow and the assessment of the consciousness function depression by the Glasgow coma scale. For those patients whose dependence was clinically apparent, the value of the linear correlation coefficient was 0.877. In patients with no apparent clinical signs of correlation, the Pearson coefficient was 0.489. Based on the results of the yugular venous oxymetry, monitoring of central hemodynamics with arteriotensometry, venotensometry, and integral bipolar rheography, the results of pulse oxymetry suggest that the main causes of the discrepancy between consciousness and the arterial cerebral inflow intensity are microcirculatory disorders and mitochondrial dysfunction that limit oxygen consumption.
Keywords: rheoencephalography; acute cerebral failure; cerebral blood flow; consciousness